PSII-9 Drylot weaned calves at dry-to-rainy transition and rainy season and their effects on the growing phase. (30th November 2020) - Nascimento, Felipe A; Prados, Laura F; Sousa, Luciana M; Oliveira, Ivanna M; Resende, Flávio D; Siqueira, Gustavo R
Abstract: The objective of this study was to determine the best nutritional strategy for weaned calves at dry-to-rainy transition and rainy season and their effects on the growing phase. One hundred sixteen Nellore weaned males (initial BW of 173±23 kg; 10 months) were used in a randomized complete block design (blocked by BW) in a 2×2 factorial arrangement of treatments (divided in 12 lots with 9 or 10 animals/lot). Factor 1 was the strategy in the dry-to-rainy season transition (period I; pasture vs. drylot) and factor 2 was the strategy for the rainy season [period II; mineral salt ad libitum (MS) vs. supplement 3 g/kg BW]; consisting of four treatments: pasture in period I and MS in period II; pasture in period I and protein-energy supplement in period II (PEII); drylot in period I and mineral salt in period II; drylot in period I and PEII. At period I, all animals received a protein-energy supplementation (5 g/kg BW). The experiment lasted 244 days. Data were analyzed using the PROC MIXED of SAS. In period I, animals from drylot had highest final BW and ADG (P < 0.01; Table 1). There was no interaction among factors (P ≥ 0.772) in period II. In period II, ADG and carcass gain were highest from pasture animals (P < 0.01). Final BW and HCW were similar (P >0.788) at the end of period II, showing that animals recovery BW. Among strategies at rainy season, animals fed PEII had greater final BW and ADG (P < 0.01). Overall growing phase, HCW and carcass gain were greater for animals fed PEII (P < 0.01). Regardless of the strategy used in the dry-to-rainy season transition, animals were able to equalize final BW at the end of growing phase. In addition, protein-energy supplement at rainy season improves animal performance at the end of growing phase.